The Role of Operational Performance as a Mediator in the Influence of Supply Chain Management Practices on the Financial Performance of MSMEs - Rubiyatno, Rubiyatno; Theodorus, Sutadi (Journal of Business & Applied Management, 2024)
Financial performance is a tool for measuring the success of a business. Managers can make appropriate decisions by reviewing the results of the company's financial performance. One of the aspects believed to influence the financial performance of a company is operational performance. Of course, this must be done through supply chain management practices in order to achieve good financial performance of the company. This research aims to determine the mediating role of company operational performance in the influence of supply chain management (SCM) practices on company financial performance. A quantitative approach was carried out by distributing questionnaires to 100 business leaders. Primary data consists of the results of filling out a questionnaire by the business owner. The data collection technique uses a survey method by distributing questionnaires to respondents, namely business owners. The MSMEs in question are 100 MSMEs located in Yogyakarta. Validity and reliability tests are carried out before implementing research analysis techniques. In this research, we examine the effect of SCM practices on financial performance through the operational performance of micro, small and medium enterprises in Bantul Regency, Yogyakarta Special Region (UMKM). The analysis technique uses structural equation modeling-partial least squares (SEM-PLS) with the WrapPLS application. The researchers estimated the results of direct effects and indirect effects. The research results prove that operational performance as a mediator in SCM practices influences the financial performance of the company. Apart from this, it is also proven that supply chain management has influence on operational performance, operational performance has influence on financial performance and supply chain management also has a direct influence on financial performance.